Prevalence of NCD Risk Factors Among the Adult Family Members of Students of School (Phase – A) - Mondal, Ratindra Nath; Das, Anupom; Islam, Md Foyzul; Podder, Priyanka; Pramanik, Soma; Rani, Moni (Journal of Medicine, 2019)
Background: Like other developing countries, in our country major causes of mortality is shifted from communicable to non-communicable diseases. NCD already disproportionately affect low and middle income countries, where nearly three quarters of NCD deaths (28 million) occur annually. Management of the existing NCD and upcoming NCD will be a great challenge for the developing countries like us. Therefore a strategy of prevention of NCD is very important. Materials and methods: This was a community based prospective interventional study, carried out in Mornea high school and Alef Uddin Sarker high school of Rangpur sadar. In the first phase, from each school 100 students from different classes were selected randomly. Then adult family members of these students were surveyed to see the prevalence of NCD risk factors. In second phase (ongoing) school health education will be given in Mornea high school (randomly chosen) monthly basis for 12 months and the students will share these with their family members. On the other hand the other school’s students will not provide any health education. One of the guardian from each family will chosen for confirmation of the sharing of information of school health education acquired by students over phone after each class. After one year prevalence of NCD risk factors will be surveyed again to know whether there are any significant differences of outcome of school health education. Results: In this study we have been able to study of 356 adult people of both sexes. From the Mornea high school 197 (55.3%) and Alef Uddin Sarker high school 159 (44.7%). Mean age of the study population was 47.33 years and female was more than male 66.3%. Awareness of NCD was found in only 10.4% of the study population. Overall 96.63% had NCD risk factors, 30.90% had two risk factors and 50.26% had 3 or more risk factors. Overall prevalence of smoking was 36.8%, among them 20.5% were current smoker. 33.1% of the study population used to take smokeless tobacco. Among the survey population only 14.3% used to take vegetables 7 days/week. 32.6% (116) people were physically inactive and 6.7% (24) had sedentary lifestyle. Only 5.3% of the people were obese and 66.57% had central obesity. Prevalence of hypertension and diabetes among the study population was 28.9% and 4.77% respectively. Among the known hypertensive 72.7% (16) used to take antihypertensive drug regularly and blood pressure was controlled in only 27.3%. Among the known diabetic mean duration were 4.12 years and 62.5% (5) of the patients used to take the antidiabetic drug regularly. Conclusions: In our study, awareness of NCD is very low but high prevalence of NCD risk factors, which are modifiable. So, an appropriate intervention is needed to modify the risk factors and thus prevention of NCDs. J MEDICINE JAN 2020; 21 (1) : 8-13